Urban scripting audio-visual forms of storytelling in urban design and planning: the case of two activity streets in Johannesburg - Mkhabela, Solam (My University, 2024)
South African cities reflect spaces based on Euro-American theories and norms, mapping methods, and design imperatives. At a local level, this imposition’s tool of static diagrams, plans, sections, elevation, and aerials; broader spatial plans with localized frameworks; regulatory plans controlling land use results in spaces hindering socio-economic development, especially for the marginalized, which comprises a predominantly black African and poor cohort. Consequently, current practice must significantly improve a city’s engagement with everyday users. Based on the indicated need, this thesis argues that the first step to effective urban design is accurately ascertaining spatial needs. In responding to current city-making practices that create ineffective spatial outputs, the study introduces Urban Scripting as a novel transdisciplinary and practice-based approach for assessing inhabitable urban locations. Its methodology in city-making processes strategically inserts social narrative to enhance understanding of daily user experiences. In creating accessible ways of exposing urban layer details, the procedures combine Nguni oral tradition (local expertise) with audio-visual (disciplinary knowledge) as a hybrid narrative technique that simultaneously analyzes and produces. Here narrative suggests using story to amplify an evolving discourse unit that writes and communicates spatial imagination. More so, storytelling, framed in and through interaction, finds people and information often missed by conventional mapping and assessment tools, specifically the voices in the ‘twilight zone,’ the space between legal and illegal on-the-ground operations. Transdisciplinary methods structure more critical and empirically on-ground evidence that inductively leads to new ways of thinking and analyzing. Practice-based casework turns space into place, builds an anthology of empirical knowledge to inform city-making methodologies, and shapes appropriate policies supporting subaltern communities. Programmatically and polemically, it explores how a cinematic frame is an inclusive tool within a specific set of urban processes. Ultimately, its enframing application calibrates an empathetic narrative, potentially transforming lives better for an African city in motion. This approach is valuable for practitioners as a firm departure from convention and thrusts Black African knowledge to the forefront, thus acting as a decolonization tool. Tested at two different sites in Johannesburg, Alexandra (formerly a Black dormitory ‘township’) and Orange Grove (once a whites-only area), the approach effectively engaged with spatial users, specifically, the microentrepreneurs whose urban insurgency practiced on the side of the street serves the broader public yet remains unnoticed by spatial practice. Urban Scripting’s methodology better understood the urban spatial challenges and needs at the Johannesburg study sites. For spatial practice site assessment, theory building, and iv practical application, it is an approach that is likely to prove equally effective in communicating bottom-up needs to help imagine and design a fair and democratic city in hundreds of other similar environments in South Africa and indeed, across Africa, where parallel realities exist.
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2023
Keywords: Urban design; Urban scripting